Un architecte hygiéniste au service de l’Hôpital général de Paris à la fin du xviiie siècle - Marc Lauro (In Situ)
Charles-François Viel (1745-1819) was the last official incumbent of the charge of architect of the General Hospital of Paris, prior to the disappearance of this institution in 1790.2 He pursued his career during the early years of the nineteenth century as architect for the capital’s civic hospices. With other colleagues, he participated in the medicalisation of the vast built heritage of the former General Hospital and of religious establishments confiscated during the Revolution as national properties. During the period of the Thermidorean Convention, he was placed at the disposition of the Seine department. In this position, he was commissioned to build or maintain numerous hospital buildings, many of which disappeared in the early years of the twentieth century, like the Cochin Hospice or the Pitié infirmary. Our article pays special attention to the work undertaken by Viel in order to supply fresh water and remove wastewater at two of the General Hospital’s main Paris sites, the Salpêtrière and the Bicêtre which, on the eve of the Revolution, accommodated 8,000 and 10,000 occupants respectively.